2021
DOI: 10.1037/ccp0000697
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Body Project eating disorder prevention program for different racial and ethnic groups and an evaluation of the potential benefits of ethnic matching.

Abstract: Objective: Provide an adequately powered tests of whether a group-delivered dissonance-based eating disorder prevention program (Body Project) is similarly effective for different racial and ethnic groups and evaluate whether an improved match between minority participant race/ethnicity and fellow group members is associated with larger effects. Method: Study 1 examined data from 539 young women from seven high schools and four universities and Study 2 examined data from 1,195 young women and men from 50 unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Regarding research directions, it would be useful for future randomized trials to manipulate the factors that were found to correlate with larger intervention effects (e.g., virtual vs. in-person administration of the Body Project ) because experiments permit firmer inferences. It would also be useful for future studies to investigate other methods of increasing the intervention effects of eating disorder prevention programs, such as by reducing alternative cognitive risk factors for eating disorders, other than thin-ideal internalization, that show more potent relations to future onset of eating disorders and predict all four types of eating disorders (e.g., appearance overvaluation and fear of weight gain vs. pursuit of the thin beauty ideal; Stice et al, 2021). More broadly, it would be useful to conduct systematic research regarding how to optimize the intervention effects of prevention programs for other health and mental health problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding research directions, it would be useful for future randomized trials to manipulate the factors that were found to correlate with larger intervention effects (e.g., virtual vs. in-person administration of the Body Project ) because experiments permit firmer inferences. It would also be useful for future studies to investigate other methods of increasing the intervention effects of eating disorder prevention programs, such as by reducing alternative cognitive risk factors for eating disorders, other than thin-ideal internalization, that show more potent relations to future onset of eating disorders and predict all four types of eating disorders (e.g., appearance overvaluation and fear of weight gain vs. pursuit of the thin beauty ideal; Stice et al, 2021). More broadly, it would be useful to conduct systematic research regarding how to optimize the intervention effects of prevention programs for other health and mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, it is the only prevention program that has reduced future onset of a psychiatric disorder, produced effects in both efficacy and effectiveness trials, produced effects that persist for 3 years, outperformed credible alternative interventions, and produced independently replicated effects (Stice et al, 2019). It is also the only eating disorder prevention program that has significantly reduced eating disorder risk factors and symptoms in randomized trials for various racial and ethnic groups in several countries, heterosexual and nonheterosexual females and males, and participants ranging in age from 11 to 64 in trials at middle schools, high schools, and universities (AlShebali et al, 2021;Brown & Keel, 2015;Brown et al, 2017;Casasnovas et al, 2019;Rodriguez et al, 2008;Rohde et al, 2014Rohde et al, , 2017Shaw et al, 2020;Stice et al, 2021;Unikel-Santoncini et al, 2019). These results imply that it might be a particularly good candidate for broad implementation.…”
mentioning
confidence: 99%
“…The Body Project consisted of four weekly 1-hr group sessions with five to nine participants delivered by peer educators using a scripted intervention manual. This version of the intervention was developed for implementation by peer educators or clinicians and was used in past trials (Stice, Rohde, et al, 2017, 2020, 2021). Participants voluntarily engaged in verbal, written, and behavioral exercises in which they critiqued the thin appearance ideal in session and completed home exercises.…”
Section: Methodsmentioning
confidence: 99%
“…One meta-analysis found a large effect size for client preferences and moderate effect size for client perceptions of therapists that favor matching but a very small effect size (.09) for psychotherapy outcomes (Cabral & Smith 2011). Another recent study by Stice et al (2021) did not find evidence that ethnoracial matching within a sample with body shape concerns (N = 1,195) was associated with larger intervention effects. As such, we did not form a priori hypotheses for an effect of client-therapist match on psychotherapy outcomes.…”
Section: Background For Present Studymentioning
confidence: 99%